Perancangan Sistem Informasi Warehouse Berbasis Visual Basic 6.0 - Muhtajuddin Danny (Jurnal SIGMA, 2021)
The rapid technological development of today has caused a very wide impact for various aspects of human life. One such impact is the increasing need for information. The increasing need for information is marked by the increasingly widespread media that provides more accurate information. This study aims to assist the Design of Information Systems Warehouse Based Visual Basic 6.0. Excellence inventory information system designed is able to store all inventory transaction data quickly, error free and can produce information. Inventory information system is made using Visual Basic 6.0 language with database system using Microsoft Access. This system serves to regulate the flow of goods in and out. After the creation of inventory information system application, it is concluded that the method of computer-based information system is very profitable for the company, because in addition to saving, stored data more secure. Keywords: Information System, Stock, database, Visual Basic 6.0.